Laser Raman Light-Scattering Observations of Conformational Changes in Myosin Induced by Inorganic Salts - Barrett, Terence W. (1978)
The Raman spectra of aqueous solutions of myosin and mixtures of myosin in solutions of the salts CaCl(2), MgCl(2), and LiBr have been taken. The spectrum of the solvent background has been subtracted by means of a computer, leaving only the Raman peaks of the protein. From an analysis of the Raman bands in the regions at 900, 940, 1,240-1,300, and 1,650-1,670 cm(-1), it seems likely that CaCl(2) effects an α-to β-transition in myosin, probably owing to the interaction of the Ca(2+) ion, LiBr appears to denature the protein leading to increased random coil structure, and MgCl(2) appears to have an effect intermediate between the two other salts. These results are reported for concentrations as low as 10(-5) M of CaCl(2) and MgCl(2). This investigation indicates the usefulness of the Raman light-scattering technique for the study of protein conformational changes.